Effects of temperature on the germination of green algae micro-propagules in coastal waters of the Subei Shoal, China. (20th September 2015) - Song, Wei; Peng, Keqin; Xiao, Jie; Li, Yan; Wang, Zongling; Liu, Xiangqing; Fu, Mingzhu; Fan, Shiliang; Zhu, Mingyuan; Li, Ruixiang
Abstract: Since 2007, large-scale green tides that primarily consisted of Ulva prolifera have consecutively invaded the coast of Qingdao (36°06'N, 120°25'E, PR China) in summer. The germination of green algae micro-propagules in the Subei Shoal played a significant role in the formation of these green tides. The change in sea temperature might be the key factor that affects the germination of the micro-propagules because the other environmental factors varied only slightly according to previous studies. This study was designed to investigate the effects of temperature on the germination of micro-propagules via laboratory experiments. The results showed the following: (1) five types of green algae micro-propagules, including U. prolifera, U. linza, U. compressa, Ulva sp. (Clade 6) and Blidingia sp., were detected in the seawater samples collected from the Subei Shoal; (2) at 5 °C, germinated micro-propagules were not detected in any of the samples; at 10 °C, the micro-propagules began to germinate, and the germination quantity markedly changed between 10 °C and 30 °C; (3) the germination numbers of U. prolifera, U. linza, Ulva sp. (Clade 6) and Blidingia sp. were maximized at 15 °C, 10 °C, 25 °C and 20 °C, respectively. This study indicated that the sea temperature played a significant role in the germination of green algae micro-propagules in water and could partly explain the community succession phenomenon of the attached green algae in the Subei Shoal. Graphical Abstract: Highlights: The germination quantity of micro-propagules changed under various temperatures. 5 kinds of green algae micro-propagules co-existed in waters of the Subei Shoal. Ulva prolifera micro-propagules germinated abundantly from 10 °C to 20 °C.